Effect of local desmopressin administration on quality of the surgical field during endoscopic sinus surgery - يوسف يوسف; دليله علاء (Latakia University Journal -Medical Sciences Series, 2021)
Background : Functional endoscopic sinus surgery became the most acceptable and performed technique in the last two decades especially for patients with chronic rhinosinusitis with or without nasal polyps , and Bleeding during functional endoscopic sinus surgery always been a challenge for the quality of surgical field for surgeons. This study aimed to evaluate the effect of local nasal desmopressin premedication on the quality of surgical field in functional endoscopic sinus surgery. Methods : This study was conducted on 60 patients with chronic rhinosinusitis who were candidate for endoscopic sinus surgery. They were assigned to two groups of 30 patients . One group ( the desmopressin ) received a single puff of local desmopressin (10 μg) in each side of nasal cavity 30 min before the surgery and the other ( the control ) received normal saline instead. the quality of the surgical field were determined in 15, 30, 60 and 90 min during the surgery (scoring by BOEZAART grading system). All data were analyzed. Results : The quality of the surgical field in the desmopressin group was better than it in the control group with p value < 0.001 in all cutoff points (15, 30, 60, and 90 min during the surgery ) and Surgeons were more satisfied with the surgical field in the desmopressin group than control group . No side effects were observed using local desmopressin. Conclusions : Premedication with local desmopressin can reduce bleeding effectively and raise the quality of the surgical field during functional endoscopic sinus surgery.